Personality y academic emotional exhaustion in peruvian college students: a predictive study - Prada Chapoñan, Rony (2020)
Introduction and objectives: Personality is a relevant feature to predict the student’s academic behavior, and its association with academic emotional exhaustion is still a recent topic. The aim was determine the predictive ability of personality on academic emotional exhaustion in 453 college students (60.9% women) between ages 17 and 40 years old, who were assessed with the Emotional Exhaustion Scale and the Big Five Inventory-15p. Was implemented a regression multiple analysis on emotional exhaustion, with the personality traits as predictors. The findings shows that the personality traits explain significantly the emotional exhaustion (R2 > .20), and the neuroticism, extraversion and consciousness predict the emotional exhaustion. In conclusion, the predictive ability of personality on academic emotional exhaustion is significant. The practical consequences and limitations are discussed.